Extended Case Method (ECM) in social and cultural research - Firdaus, Firdaus; Shalihin, Nurus (ETNOSIA : Jurnal Etnografi Indonesia, 2021)
This article aims to introduce the Extended Case Method (ECM) as an approach to qualitative social research. As an approach, the ECM rooted in the ethnography approach in the anthropological tradition and developed in the sociological tradition research. With reference to Michael Buroway (1998) as a developer of ECM and some articles that used ECM as a method, this paper outlines the basic concepts of ECM, their advantages and infirmity, and the application of theories in social research by using ECM. As an extended case, there are four aspects that extend on ECM, namely intervention, processes, structuration, and reconstruction (theory). The advantage of ECM is their four extending. Rather than the infirmity of ECM rooted from their advantage, namely domination, silencing, objectification, and normalization. The use of theory in ECM was carried out from the beginning to the end of the study. Base on their characteristics, ECM very feasible to use to understanding borderless society and ambiguity of case study on research of social science in general, and ethnography especially.